The Influence of Community-Based Participation on Sustainable Tourism Development: Mediating Effect of Local Support through a Structural Equation Modelling Approach - Yousaf, Hina; Javed, Tasawar (Pakistan Journal of Humanities and Social Sciences, 2025)
This study investigates the dynamic relationship between the community-based participation (CBP) and sustainable tourism development (STD), with the particular focus on mediating role of the local support. The core objective of this current study, is to explore that how society involvement contributes in the effectiveness of sustainable tourism initiatives. On the bases of primary data collected through an empirical survey of 150 local residents from south Punjab of Pakistan. This study also helps to reveals the significant and positive connection between the community-based participation and sustainable tourism development. The simple random sampling technique applies for this study. Furthermore, the finding of this study indicate that local support mediates this relationship and suggesting the main acting endorsement and involvement of the local people help to enhance the sustainability of the tourism development. The results of this study, underscore the importance of inclusive community involvement which helps to impower the local stakeholders and local leaders to make the successful tourism outcomes. The theocratical implementation of this study adds the value by demonstrating the local support operate as a critical intermediary, reinforcing the link between the local people’s involvement and sustainable tourism practices.